Field emission investigation of composites of polypyrrole with graphene oxide, reduced graphene oxide and graphene nanoribbons - Harpale, Kashmira; Bansode, Sanjeewani; More, Mahendra; Late, D. J. (2016 29th International Vacuum Nanoelectronics Conference (IVNC), 2016)
The monomer pyrrole has been polymerized by chemical route in the presence of graphene oxide (GO), reduced graphene oxide (rGO) and graphene nanoribbons (GNR) separately to prepare nanocomposites as Polypyrrole-GO (PGO), PPy-rGO (PRGO), PPy-GNR (PGNR), respectively. The morphological, chemical and structural characterization of the as-synthesized products was carried out using scanning electron microscopy (SEM), Raman and fourier transform infrared (FTIR) spectroscopy. Field emission (FE) studies of PGO, PRGO, PGNR emitters were performed at the base pressure of 1x10(-8) mbar in planar `diode' configuration. Onset and threshold field values corresponding to emission current densities of 1 and 100 mu A/cm(2) are observed to be 1.5 and 2.3V/mu m for PGO, 1.4 and 2.2 V/mu m for PRGO and lowest for PGNR as 0.9 and 1.2V/mu m, respectively. The maximum emission current density of 2.5 mA/cm(2) drawn for PGO at the applied electric field of 3.2V/mu m, 1.2 mA/cm(2) at 3.6V/mu m from the PRGO and 8 mA/cm(2) at the field of 2.2 V/mu m from the PGNR emitters. An emission current versus time (I-t) plot shows stable emission behavior for the preset current values.
Keywords: field emission; FTIR; polypyrrole; Raman

Enhanced field emission performance of NiMoO4 nanosheets by tuning the phase - Bankar, P. K. (Applied Surface Science, 2017)
In this paper we report, large scale synthesis of α and β-NiMoO4 by a facile hydrothermal method and we observed that urea plays important role on the growth of β-NiMoO4 nanosheets. We have also carried out field emission (FE) investigations of α and β-NiMoO4 at a base pressure of ∼1 × 10−8 mbar. The obtained turn-on field at emission current density of 1 μA/cm2 for β-NiMoO4 nanosheets and α −NiMoO4 is 1.3 V/μm and 2.2 V/μm respectively were observed. The maximum field emission current density of 1.006 mA/cm2at an applied electric field of 2.7 V/μm was achieved for β-NiMoO4 nanosheets. Furthermore, we found that the β-NiMoO4 nanosheets possess good field emission performance compared to α-NiMoO4. The results indicate that NiMoO4can be used as a promising material in FE applications with possibility of tuning field emission performance by controlling the phase.
Keywords: Current stability; field emission; nanosheets; NiMoO4

VSe2-reduced graphene oxide as efficient cathode material for field emission - Ratha, S. (Journal of Physics and Chemistry of Solids, 2019)
Field emission properties of pristine VSe2 and its hybrid with reduced graphene oxide (RGO) have been investigated in detail. Promising field emission performance were noted with lower values of turn-on and threshold fields of ∼1.3 V μm−1 and 2.12 V μm−1 respectively for the VSe2/RGO hybrid which is much more superior than that of pristine VSe2 emitter and other 2D materials. Density Functional Theory (DFT) simulations have also been performed to qualitatively support our experimental observations through demonstration of Density of States and computation of work function for pristine VSe2 and hybrid VSe2/RGO. The lowering of work function and appearance of additional states near Fermi level from carbon p orbital of RGO is responsible for superior field emission characteristics in hybrid VSe2/RGO compared to pristine VSe2 which supports our experimental observations. Our experimental data and theoretical insight from electronic structure simulations strongly infer that the synthesized hybrid VSe2/RGO has the potential to be tailored as efficient and high performance cathode material in field emission based devices.
Keywords: cathode material; Chalcogenide; Density functional theory; field emission; Vanadium diselenide; Work function